Avaliação da composição corporal de indivíduos obesos candidatos à cirurgia bariátrica - Alves, Letícia Biscaino (2016)
Introduction: The indication for bariatric surgery based on body mass index is being questioned due to the fact that it does not take body composition into consideration. Objective: Determine the patient's body composition prior to indicating bariatric surgery. Methods: Being included in the study, were patients treated at the Center for Obesity and Metabolic Syndrome at Hospital São Lucas da PUCRS for obesity. Body composition was measured by using an Bioelectrical impedance analysis device, model InBody 770. For the analysis of data, body fat percentage, lean mass percentage, waist, waist/hip ratio, visceral fat area, BMI and surgical indication were considered. Results: A total of 407 subjects were evaluated, 87 (21.4%) men, with the mean age being 36 years. In men, with and without indication for bariatric surgery, BMI, body fat percentage and visceral fat area were 44.3 kg/m² and 34.2 kg/m² (P <0.001), 45.1% and 37.6% (P = 0.001), 243.6 cm² and 187.5 cm² (P <0.001), respectively. In women, with and without indication for bariatric surgery, BMI, body fat percentage and visceral fat area were 42.2 kg/m² and 34.6 kg/m² (P <0.001), 50.7 % and 46.7 % (P < 0.001), 241.7 cm² and 204.2 cm² (P <0.001), respectively. Conclusion: This study showed a significant difference in body composition between men and women, among the obese with and without indication for bariatric surgery.